Next-Generation Sequencing-Based Clonality Assessment of Ig Gene Rearrangements: A Multicenter Validation Study by EuroClonality-NGS - van den Brand, Michiel; Rijntjes, Jos; Möbs, Markus; Steinhilber, Julia; van der Klift, Michèle Y; Heezen, Kim C; Kroeze, Leonie I; Reigl, Tomas; Porc, Jakub; Darzentas, Nikos; Luijks, Jeroen A C W; Scheijen, Blanca; et al. (The Journal of molecular diagnostics, 2021)
Ig gene (IG) clonality analysis has an important role in the distinction of benign and malignant B-cell lymphoid proliferations and is mostly performed with the conventional EuroClonality/BIOMED-2 multiplex PCR protocol and GeneScan fragment size analysis. Recently, the EuroClonality-NGS Working Group developed a method for next-generation sequencing (NGS)-based IG clonality analysis. Herein, we report the results of an international multicenter biological validation of this novel method compared with the gold standard EuroClonality/BIOMED-2 protocol, based on 209 specimens of reactive and neoplastic lymphoproliferations. NGS-based IG clonality analysis showed a high interlaboratory concordance (99%) and high concordance with conventional clonality analysis (98%) for the molecular conclusion. Detailed analysis of the individual IG heavy chain and kappa light chain targets showed that NGS-based clonality analysis was more often able to detect a clonal rearrangement or yield an interpretable result. NGS-based and conventional clonality analysis detected a clone in 96% and 95% of B-cell neoplasms, respectively, and all but one of the reactive cases were scored polyclonal. We conclude that NGS-based IG clonality analysis performs comparable to conventional clonality analysis. We provide critical parameters for interpretation and discuss a first step toward a quantitative scoring approach for NGS clonality results. Considering the advantages of NGS-based clonality analysis, including its high sensitivity and possibilities for accurate clonal comparison, this supports implementation in diagnostic practice.
Keywords: Sensitivity and Specificity; senzitivita a specificita; Immunoglobulin Heavy Chains; Humans; buněčné klony; Data Accuracy; Lymphoma, B-Cell; Phenotype; Multiplex Polymerase Chain Reaction; správnost dat; lidé; Immunoglobulin kappa-Chains; těžké řetězce imunoglobulinů; multiplexová polymerázová řetězová reakce; B-lymfocyty; geny pro imunoglobuliny; Clone Cells; Genes, Immunoglobulin; fenotyp; B-buněčný lymfom; B-Lymphocytes; Lymphoma, Follicular; vysoce účinné nukleotidové sekvenování; Gene Rearrangement; High-Throughput Nucleotide Sequencing; genová přestavba; folikulární lymfom; imunoglobuliny - kappa-řetězce